Personal Branding terhadap Sosial Media - Desta Arya Puspita (IPM2KPE, 2022)
This study aims to determine the influence and way of carrying personal branding from Indonesian content creator Atta Halilintar through uploading his YouTube video. This research method is descriptive qualitative. The results showed that Atta Halilintar really cares about himself as a personal branding which includes, a) personality; b) Style and style; c) selection of outfits and infits with well-known brands, d) creativity in creating works. This made him a success known to many people and dubbed the king of youtube. In conclusion, Atta Halilintar's personal branding is also a strong personal branding element because it has unique values ​​and personalities that are different from the content of other male creators. His personal branding is related to the needs of his target group and is consistently built on social media with linear content that reflects his personal branding. Keywords: Personal branding, Content creator, King of Youtube